Os conhecimentos prévios no letramento literário - Silva, Josiane Tavares (2015)
The present research investigates the construction of singular readings with the stimulation of creativity, noting the role of previous knowledge in these readings in literature class of activities from the literary literacy. In order to carry out the proposed investigation, we proceed to the study of some theoretical approaches to literacy, literary literacy and previous knowledge, as well as a field of study with students of the 8th grade of elementary school in a peripheral public school. During lessons, we applied questionnaire on literature practices and tests of reading skills, and we realized lessons from the practice of literary literacy, from which we obtained the following productions of the students: retelling Little Red Riding Hood, creating investigative character, questions about previous knowledge about matters at hand. This research conducts an observation of literary cultural context to which students are exposed and a comparison of the literature practices of two of the students surveyed. As methodological guidelines have mainly interpretive, using the quantitative analysis of certain data; the dialectical approach, analyzing the problem in broader aspects of the classroom everyday and the method of action research procedure, which allowed the teacher to act investigating a problem of reality of their teaching environment in the teaching-learning process . We seek to better understand the literary cultural context in which students are entered, which would represent a bit of their previous knowledge, and understand the role of previous knowledge of students in literary literacy